Implementation of SAK EMKM financial statements, water filter technology, and digital marketing communication in sorong regency's outstanding MSMEs - Munzir Munzir; Ainul Alim; Juminah Juminah; Okid Parama Astirin; Elvi Litcia; Ial Ramadhan; Nirmalani Muzdalifah; Frans Rudolof Mender; Annisa Latifah Qolbiyanti (Journal of Community Service and Empowerment, 2025)
The service activity is driven by the need to strengthen the capacity and competitiveness of exceptional MSMEs in Sorong Regency. This service activity offers a substantial contribution to the development of excellent MSMEs in Sorong Regency by employing SAK EMKM to create simple yet responsible financial statements, water filter technology helps MSMEs obtain clean water sources, digital marketing communication training increases MSMEs' ability to promote their products more extensively and effectively, leveraging digital platforms to access new markets and increase competitiveness. The methods employed in this service activity include a participative and educational approach with stages consisting of socialization, training, mentorship, and evaluation. The socialization was held to teach the necessity of implementing SAK EMKM, water filter technology, and digital marketing communication to outstanding MSME players in Sorong Regency. The methods employed in this service activity include a participative and educational approach with stages consisting of socialization, training, mentorship, and evaluation. Combining three important areas financial reporting, technology, and digital marketing worked well to solve the common problems that SMEs encounter. This program not only improves professionalism and product quality, but it also increases the chances of corporate growth and long-term success.